Polarizing plate and image display device using the polarizing plate
By adopting the structure of an iodine-containing polyvinyl alcohol-based resin layer, a transparent protective film and a urea-based compound layer in the polarized plate and adjusting its moisture content, the problem of significantly reducing the permeability of the polarized plate under high temperature environment is solved, and the high permeability and high temperature resistance of the polarized plate at high temperature is achieved.
Patent Information
- Application Number
- JP2020188521
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-15
- Filing Date
- 2020-11-12
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2040-11-12
AI Technical Summary
In a high temperature environment, the polarized plate with an interlayer filling structure is significantly reduced in liquid crystal display devices and organic light emitting diode display devices.
A polarized plate containing a polyvinyl alcohol-based resin layer and a transparent protective film containing adsorption and directional iodine is used, and a urea-based compound layer is added to the polarized plate to adjust the moisture content of the polarized plate so that it reaches equilibrium within the range of 20°C and a relative humidity of 30% to 50%.
In high temperature environment, the degree of reduction in mittance of the polarized plate is significantly reduced, maintaining high high-temperature resistance and stability, avoiding the problem of significant reduction in mittance of the polarized plate when used at high temperatures.
Smart Images

Figure 0007671133000001 
Figure 0007671133000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate, and further to an image display device in which one surface of the polarizing plate is bonded to an image display cell and the other surface is bonded to a transparent member such as a touch panel or a front panel. [Background technology]
[0002] Liquid crystal display devices (LCDs) are widely used not only in liquid crystal televisions, but also in personal computers, mobile devices such as mobile phones, and in-vehicle applications such as car navigation systems. Typically, liquid crystal display devices have a liquid crystal panel member in which polarizing plates are attached to both sides of a liquid crystal cell with an adhesive, and display is performed by controlling light from a backlight member with the liquid crystal panel member. In addition, organic electroluminescence (EL) display devices have also been widely used in recent years in mobile devices such as televisions and mobile phones, and in-vehicle applications such as car navigation systems, similar to liquid crystal display devices. In organic EL display devices, a circular polarizing plate (a laminate including a polarizing element and a λ / 4 plate) may be disposed on the viewing side surface of the image display panel in order to prevent external light from being reflected by a metal electrode (cathode) and being viewed as a mirror surface.
[0003] As mentioned above, polarizing plates are increasingly being installed in vehicles as components of liquid crystal display devices and organic electroluminescence display devices. Polarizing plates used in vehicle-mounted image display devices are more often exposed to high-temperature environments than those used in other mobile applications such as televisions and mobile phones, and are therefore required to have small changes in properties at high temperatures (high-temperature durability). On the other hand, for the purpose of preventing damage to the image display panel due to impact from the outer surface, a configuration in which a front plate such as a transparent resin plate or a glass plate (also referred to as a "window layer" or the like) is provided on the viewing side further than the polarizing plate of the image display panel is becoming more common. Also, in display devices equipped with a touch panel, a configuration in which a touch panel is provided on the viewing side further than the polarizing plate of the image display panel and a front plate is provided on the viewing side further than the touch panel is widely adopted.
[0004] In such a configuration, if there is an air layer between the image display panel and a transparent member such as a front plate or a touch panel, the light reflection at the interface of the air layer causes reflection of external light, which tends to reduce the visibility of the screen. Therefore, there is a growing trend to adopt a configuration in which the space between the polarizing plate and the transparent member arranged on the viewing side surface of the image display panel is filled with a layer other than the air layer (hereinafter, sometimes referred to as an "interlayer filler"), preferably a material with a refractive index close to that of the above material (hereinafter, sometimes referred to as an "interlayer filler configuration"). As the interlayer filler, a pressure sensitive adhesive or a UV curable adhesive is used for the purpose of suppressing the decrease in visibility due to reflection at the interface and bonding and fixing each member (see, for example, Patent Document 1).
[0005] The above-mentioned interlayer filling structure is being widely adopted for mobile applications such as mobile phones that are often used outdoors. In addition, due to the increasing demand for visibility in recent years, the adoption of an interlayer filling structure in which a front plate is placed on the surface of an image display panel and an adhesive layer or the like is filled between the panel and the front plate is being considered for in-vehicle applications such as car navigation devices. However, when such a configuration is adopted, it has been reported that the results of a heat durability test (e.g., at 95°C for 200 hours) show a significant decrease in transmittance in the center of the polarizing plate surface, whereas the polarizing plate alone does not show a significant decrease in transmittance even after 1,000 hours at 95°C. Based on these results, it has also been reported that the significant decrease in transmittance of the polarizing plate in a high-temperature environment is a problem specific to the case where an image display device employing an interlayer filling configuration in which one surface of the polarizing plate is bonded to an image display cell and the other surface is bonded to a transparent member such as a touch panel or front panel is exposed to a high-temperature environment (Patent Document 2).
[0006] In addition, in the above-mentioned Patent Document 2, a polarizing plate with a significantly reduced transmittance due to an interlayer filling structure was measured by Raman spectroscopy at 1100 cm -1 near (derived from the C-C bond) and 1500 cm -1 Since there is a peak near the -C=C bond, it is considered to be a polyene structure (-C=C). n-, and it is presumed that this is the result of the polyvinyl alcohol that constitutes the polarizing element being dehydrated to form a polyenen (Patent Document 2, paragraph
[0012] ).
[0007] As a solution to this problem, Patent Document 2 proposes a method of suppressing the decrease in transmittance by keeping the moisture content per unit area of the polarizing plate below a specified amount and keeping the saturated water absorption amount of the transparent protective film adjacent to the polarizing element below a specified amount. However, even with such measures, the effect of suppressing the decrease in transmittance in a high-temperature durability test was not sufficient. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-174417 [Patent Document 2] JP 2014-102353 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention provides the following polarizing plate, image display device, and method for producing a polarizing plate. [1] A polarizing plate having a polarizing element formed by adsorbing and aligning iodine in a polyvinyl alcohol-based resin layer and a transparent protective film, a urea-based compound-containing layer containing at least one urea-based compound selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives; The polarizing element has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. [2] A polarizing plate having a polarizing element in which iodine is adsorbed and aligned in a polyvinyl alcohol-based resin layer, and a transparent protective film, a urea-based compound-containing layer containing at least one urea-based compound selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives; The polarizing plate has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. [3] The polarizing plate according to [1] or [2], wherein the urea-based compound-containing layer contains at least one urea-based compound selected from the group consisting of urea derivatives and thiourea derivatives. [4] The polarizing plate according to any one of [1] to [3], wherein the urea-based compound-containing layer is in contact with the polarizing element. [5] The polarizing plate according to any one of [1] to [4], wherein the urea compound-containing layer is an adhesive layer. [6] The polarizing plate according to [5], wherein the urea compound-containing layer contains a polyvinyl alcohol resin. [7] The polarizing plate according to [6], wherein the total content of the urea compounds in the urea compound-containing layer is 0.1 parts by mass or more and 400 parts by mass or less with respect to 100 parts by mass of the polyvinyl alcohol resin. [8] The polarizing plate according to any one of [5] to [7], wherein the urea compound-containing layer has a thickness of 0.01 to 7 μm. [9] A polarizing plate having a polarizing element formed by adsorbing and aligning iodine in a polyvinyl alcohol-based resin layer, and a transparent protective film, the polarizing element contains at least one urea-based compound selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives; The polarizing element has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
[10] A polarizing plate having a polarizing element formed by adsorbing and aligning iodine in a polyvinyl alcohol-based resin layer, and a transparent protective film, the polarizing element contains at least one urea-based compound selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives; The polarizing plate has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
[11] The polarizing plate is used in an image display device, The polarizing plate according to any one of [1] to
[10] , wherein in the image display device, a layer other than an air layer is provided on both sides of the polarizing plate in contact with the both sides.
[12] An image display device comprising: an image display cell; a first pressure-sensitive adhesive layer laminated on a viewing-side surface of the image display cell; and the polarizing plate according to any one of [1] to
[11] laminated on the viewing-side surface of the first pressure-sensitive adhesive layer.
[13] The image display device according to
[12] , further comprising a second adhesive layer laminated on the viewing side surface of the polarizing plate, and a transparent member laminated on the viewing side surface of the second adhesive layer.
[14] The image display device according to
[13] , wherein the transparent member is a glass plate or a transparent resin plate.
[15] The image display device according to
[13] , wherein the transparent member is a touch panel.
[16] A method for producing the polarizing plate according to [1] or [9], A method for manufacturing a polarizing plate, comprising a moisture content adjusting step of adjusting the moisture content of the polarizing element so that it is equal to or higher than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50%.
[17] A method for producing a polarizing plate according to [2] or
[10] , A method for manufacturing a polarizing plate, comprising a moisture content adjusting step of adjusting the moisture content of the polarizing plate so that it is equal to or higher than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50%. Effect of the Invention
[0010] According to the present invention, it is possible to provide a polarizing plate that exhibits little decrease in transmittance in high-temperature environments and has excellent high-temperature durability even when used in an image display device with an interlayer filling configuration.Furthermore, by using the polarizing plate of the present invention, it is possible to provide an image display device in which the decrease in transmittance in high-temperature environments is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] First Embodiment The polarizing plate according to the first embodiment of the present invention includes a polarizing element formed by adsorbing and aligning iodine in a polyvinyl alcohol resin layer, a urea compound layer containing at least one urea compound selected from urea, urea derivatives, thiourea, and thiourea derivatives, and a transparent protective film. The polarizing plate according to this embodiment has at least one of the following characteristics (a) and (b). (a) The moisture content of the polarizing element is equal to or greater than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and is equal to or less than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. (b) The moisture content of the polarizing plate is equal to or greater than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and is equal to or less than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
[0012] The polarizing plate of this embodiment has at least one of the above characteristics (a) and (b), and further has a urea-based compound-containing layer, so that as a component of an image display device having an interlayer filling configuration, the polarizing plate can suppress a decrease in single-unit transmittance even when exposed to a high-temperature environment for a long period of time. The polarizing plate of this embodiment has a urea-based compound-containing layer, so that the polarizing plate can suppress a decrease in polarization degree even when exposed to a high-temperature environment. When two polarizing plates are used in a crossed Nicol arrangement, if the polarization degree of the polarizing plate decreases, light leakage (hereinafter also referred to as "cross leakage") is likely to occur. However, according to the present invention, the polarization degree is unlikely to decrease even when exposed to a high-temperature environment, so that cross leakage is also easily suppressed.
[0013] [Polarizing element] As the polarizing element of the present invention in which iodine is adsorbed and aligned in the polyvinyl alcohol (hereinafter also referred to as PVA)-based resin layer, a well-known polarizing element can be used. Such a polarizing element is generally formed by using a PVA-based resin film, dyeing the PVA-based resin film with iodine, and uniaxially stretching the PVA-based resin film.
[0014] As described above, the PVA resin is generally obtained by saponifying a polyvinyl acetate resin. The degree of saponification is about 85 mol% or more, preferably about 90 mol% or more, more preferably about 99 mol% to 100 mol%. Examples of the polyvinyl acetate resin include polyvinyl acetate, which is a homopolymer of vinyl acetate, as well as copolymers of vinyl acetate and other monomers copolymerizable therewith, such as ethylene-vinyl acetate copolymers. Examples of the other copolymerizable monomers include unsaturated carboxylic acids, olefins, vinyl ethers, and unsaturated sulfonic acids. The degree of polymerization of the PVA resin is 1000 to 10000, preferably 1500 to 5000. The PVA resin may be modified, and may be, for example, polyvinyl formal, polyvinyl acetal, polyvinyl butyral, or the like, modified with aldehydes.
[0015] The method for producing the polarizing element is not particularly limited, but is typically a method in which a polyvinyl alcohol-based resin film wound in advance into a roll is sent out and stretched, dyed, crosslinked, or the like, or a method including a step of producing a laminate of a polyvinyl alcohol-based resin and a resin substrate for stretching, and stretching the laminate. Any of these methods can be used in the present invention. The methods for producing these polarizing elements are described in paragraphs
[0109] to
[0128] of JP-A-2014-48497, and these methods can be used in this embodiment. The thickness of the polarizing element in this embodiment is preferably 3 to 35 μm, more preferably 4 to 30 μm, and even more preferably 5 to 25 μm.
[0016] (Feature (a)) In the case of having the characteristic (a), the moisture content of the polarizing element is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. More preferably, it is equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 45%, even more preferably, it is equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 42%, and most preferably, it is equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 38%. If the moisture content is lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, the polarizing element becomes less easy to handle and more likely to break. If the moisture content of the polarizing element is higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%, the transmittance of the polarizing element is more likely to decrease. It is presumed that if the moisture content of the polarizer is high, the polyenization of the PVA resin is more likely to proceed. The moisture content of the polarizing element is the moisture content of the polarizing element in the polarizing plate.
[0017] A method for checking whether the moisture content of a polarizing element is within the range of equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50% can be to store the polarizing element in an environment adjusted to the above temperature and relative humidity ranges, and if there is no change in mass for a certain period of time, it can be considered that the element has reached equilibrium with the environment. Alternatively, the equilibrium moisture content of the polarizing element in an environment adjusted to the above temperature and relative humidity ranges can be calculated in advance, and the moisture content of the polarizing element can be compared with the previously calculated equilibrium moisture content.
[0018] Methods for producing a polarizing element having a moisture content equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50% include, but are not limited to, a method in which the polarizing element is stored in an environment adjusted to the above-mentioned temperature and relative humidity range for 10 minutes to 3 hours, or a method in which the polarizing element is heated at 30°C to 90°C.
[0019] Another preferred method for producing a polarizing element having the above moisture content includes a method of storing a laminate in which a protective film is laminated on at least one surface of a polarizing element, or a polarizing plate constructed using a polarizing element, in an environment adjusted to the above temperature and relative humidity ranges for 10 minutes to 120 hours, or a method of heat treating the same at 30° C. to 90° C. When producing an image display device employing an interlayer filling configuration, an image display panel in which a polarizing plate is laminated on an image display cell may be stored for 10 minutes to 3 hours or heated at 30° C. to 90° C. in an environment adjusted to the above temperature and relative humidity ranges, and then a front plate may be attached to the image display panel.
[0020] The moisture content of the polarizing element is preferably adjusted to be within the above numerical range at the stage of the material used to construct the polarizing plate, which is a polarizing element alone or a laminate of a polarizing element and a protective film. If the moisture content is adjusted after the polarizing plate is constructed, curling may become too large, and problems may easily occur when the polarizing plate is attached to an image display cell. By constructing a polarizing plate using a polarizing element that has been adjusted to have the above moisture content at the stage of the material before the polarizing plate is constructed, a polarizing plate having a polarizing element whose moisture content satisfies the above numerical range can be easily constructed. The moisture content of the polarizing element in the polarizing plate may be adjusted to be within the above numerical range while the polarizing plate is attached to the image display cell. In this case, the polarizing plate is less likely to curl because it is attached to the image display cell.
[0021] (Feature (b)) In the case of having the characteristic (b), the moisture content of the polarizing plate is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. The moisture content of the polarizing plate is preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 45%, more preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 42%, and even more preferably equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 38%. If the moisture content of the polarizing plate is lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, the handling property of the polarizing plate is deteriorated and the polarizing plate is easily cracked. If the moisture content of the polarizing plate is higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%, the transmittance of the polarizing element is easily decreased. It is presumed that the high moisture content of the polarizing plate makes it easier for the PVA-based resin to be polyenized.
[0022] As a method for checking whether the moisture content of a polarizing plate is within the range of equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50%, it can be stored in an environment adjusted to the above temperature and relative humidity ranges, and if there is no change in mass for a certain period of time, it can be considered that the polarizing plate has reached equilibrium with the environment. Alternatively, it can be confirmed by previously calculating the equilibrium moisture content of the polarizing plate in an environment adjusted to the above temperature and relative humidity ranges, and comparing the moisture content of the polarizing plate with the previously calculated equilibrium moisture content.
[0023] Methods for producing a polarizing plate having a moisture content equal to or greater than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or less than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50% include, but are not limited to, a method in which the polarizing plate is stored in an environment adjusted to the above-mentioned temperature and relative humidity range for 10 minutes to 3 hours, or a method in which the polarizing plate is heated at 30°C to 90°C.
[0024] When producing an image display device employing an interlayer filling configuration, an image display panel having a polarizing plate laminated on an image display cell may be stored in an environment adjusted to the above-mentioned temperature and relative humidity range for 10 minutes to 3 hours or heated to 30°C to 90°C, and then a front panel may be laminated thereto.
[0025] [Urea-based compound-containing layer] The polarizing plate of the present invention has a urea-based compound-containing layer containing at least one urea-based compound selected from urea, urea derivatives, thiourea, and thiourea derivatives. The urea-based compound-containing layer is not limited as long as it contains a urea-based compound, and examples thereof include an adhesive layer and a cured layer. The urea-based compound-containing layer may or may not be in contact with the polarizing element, but is preferably in contact with the polarizing element from the viewpoint of further suppressing the decrease in transmittance in a high-temperature environment. In the present invention, from the viewpoint of productivity, it is preferable that the adhesive layer is a layer containing a urea-based compound. The adhesive layer is formed from the following adhesive. An example of the adhesive layer that is a layer containing a urea-based compound is an adhesive layer that bonds a polarizing element and a protective film. The configuration in the case where the urea compound-containing layer is other than the adhesive layer will be described later.
[0026] <Adhesive layer> The adhesive constituting the adhesive layer for bonding the protective film to the polarizing element can be any appropriate adhesive. Specifically, the adhesive can be a water-based adhesive, a solvent-based adhesive, or an active energy ray curable adhesive, but a water-based adhesive is preferred. When the adhesive layer is a layer containing a urea-based compound, the adhesive contains at least one urea-based compound selected from urea, urea derivatives, thiourea, and thiourea derivatives. The thickness of the adhesive when applied can be set to any appropriate value. For example, it is set so that an adhesive layer having a desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm to 7 μm, more preferably 0.01 μm to 5 μm, even more preferably 0.01 μm to 2 μm, and most preferably 0.01 μm to 1 μm.
[0027] (Water-based adhesive) Any suitable aqueous adhesive may be used as the aqueous adhesive. Among them, an aqueous adhesive containing a PVA resin (PVA adhesive) is preferably used. The average polymerization degree of the PVA resin contained in the aqueous adhesive is preferably about 100 to 5500, more preferably 1000 to 4500, from the viewpoint of adhesiveness. The average saponification degree is preferably about 85 mol% to 100 mol%, more preferably 90 mol% to 100 mol%, from the viewpoint of adhesiveness.
[0028] The PVA resin contained in the water-based adhesive preferably contains an acetoacetyl group, because it has excellent adhesion between the PVA resin layer and the protective film and excellent durability. The acetoacetyl group-containing PVA resin can be obtained, for example, by reacting a PVA resin with diketene by any method. The acetoacetyl group modification degree of the acetoacetyl group-containing PVA resin is typically 0.1 mol% or more, and preferably about 0.1 mol% to 20 mol%. The resin concentration of the above-mentioned water-based adhesive is preferably 0.1% by weight to 15% by weight, and more preferably 0.5% by weight to 10% by weight.
[0029] (Crosslinking agent, solvent) The water-soluble PVA adhesive preferably used in the present invention may contain a crosslinking agent as necessary in addition to the above-mentioned PVA resin and urea compound. Known crosslinking agents can be used as the crosslinking agent. Examples of the crosslinking agent include water-soluble epoxy compounds, dialdehydes, and isocyanates.
[0030] When the PVA-based resin is an acetoacetyl group-containing PVA-based resin, the crosslinking agent is preferably any one of glyoxal, glyoxylate, and methylolmelamine, more preferably any one of glyoxal and glyoxylate, and particularly preferably glyoxal.
[0031] The water-soluble PVA adhesive of the present invention may contain an organic solvent. In this case, the organic solvent is preferably an alcohol because of its miscibility with water, and among alcohols, methanol or ethanol is more preferable. In the present invention, some of the urea derivatives have low solubility in water but sufficient solubility in alcohol. In that case, one of the preferred embodiments is to dissolve the urea derivative in alcohol to prepare an alcohol solution of the urea derivative, and then add the alcohol solution of the urea derivative to the aqueous PVA solution to prepare the adhesive.
[0032] (Active energy ray curing adhesive) As the active energy ray curable adhesive, any suitable adhesive can be used as long as it is an adhesive that can be cured by irradiation with active energy rays. Examples of the active energy ray curable adhesive include ultraviolet ray curable adhesives and electron beam curable adhesives. Specific examples of the curing type of the active energy ray curable adhesive include radical curable type, cationic curable type, anionic curable type, and combinations thereof (for example, a hybrid of radical curable type and cationic curable type).
[0033] The active energy ray-curable adhesive may, for example, be an adhesive containing, as a curing component, a compound (for example, a monomer and / or oligomer) having a radical polymerizable group such as a (meth)acrylate group or a (meth)acrylamide group. Specific examples of the above-mentioned active energy ray-curable adhesive and a method for curing the same are described in, for example, JP-A-2012-144690.
[0034] (Urea-based compounds) When the adhesive layer is a layer containing a urea-based compound, the adhesive layer contains at least one urea-based compound selected from urea, urea derivatives, thiourea, and thiourea derivatives. As a method for incorporating a urea-based compound in the adhesive layer, it is preferable to incorporate the urea-based compound in the above-mentioned adhesive. Note that, in the process of forming the adhesive layer from the adhesive through a drying process, etc., it does not matter if a part of the urea-based compound migrates from the adhesive layer to the polarizing element, etc. Urea compounds include water-soluble and poorly water-soluble urea compounds, and both types can be used in the present invention. When a poorly water-soluble urea compound is used in a water-soluble adhesive, it is preferable to devise a dispersion method so that an increase in haze does not occur after the adhesive layer is formed.
[0035] When the adhesive is an aqueous adhesive containing a PVA resin, the amount of the urea compound added is preferably 0.1 to 400 parts by mass, more preferably 1 to 200 parts by mass, and even more preferably 3 to 100 parts by mass, relative to 100 parts by mass of PVA.
[0036] (urea derivative) A urea derivative is a compound in which at least one of the four hydrogen atoms of a urea molecule is substituted with a substituent. In this case, the substituent is not particularly limited, but is preferably a substituent consisting of a carbon atom, a hydrogen atom, and an oxygen atom.
[0037] Specific examples of urea derivatives include mono-substituted ureas such as methylurea, ethylurea, propylurea, butylurea, isobutylurea, N-octadecylurea, 2-hydroxyethylurea, hydroxyurea, acetylurea, allylurea, 2-propynylurea, cyclohexylurea, phenylurea, 3-hydroxyphenylurea, (4-methoxyphenyl)urea, benzylurea, benzoylurea, o-tolylurea, and p-tolylurea. Disubstituted ureas include 1,1-dimethylurea, 1,3-dimethylurea, 1,1-diethylurea, 1,3-diethylurea, 1,3-bis(hydroxymethyl)urea, 1,3-tert-butylurea, 1,3-dicyclohexylurea, 1,3-diphenylurea, 1,3-bis(4-methoxyphenyl)urea, 1-acetyl-3-methylurea, 2-imidazolidinone (ethylene urea), and tetrahydro-2-pyrimidinone (propylene urea). Examples of 4-substituted ureas include tetramethylurea, 1,1,3,3-tetraethylurea, 1,1,3,3-tetrabutylurea, 1,3-dimethoxy-1,3-dimethylurea, 1,3-dimethyl-2-imidazolidinone, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone.
[0038] (Thiourea derivatives) A thiourea derivative is a compound in which at least one of the four hydrogen atoms of a thiourea molecule is substituted with a substituent. In this case, the substituent is not particularly limited, but is preferably a substituent consisting of a carbon atom, a hydrogen atom, and an oxygen atom.
[0039] Specific examples of thiourea derivatives include mono-substituted thioureas such as N-methylthiourea, ethylthiourea, propylthiourea, isopropylthiourea, 1-butylthiourea, cyclohexylthiourea, N-acetylthiourea, N-allylthiourea, (2-methoxyethyl)thiourea, N-phenylthiourea, (4-methoxyphenyl)thiourea, N-(2-methoxyphenyl)thiourea, N-(1-naphthyl)thiourea, (2-pyridyl)thiourea, o-tolylthiourea, and p-tolylthiourea. Examples of the disubstituted thiourea include 1,1-dimethylthiourea, 1,3-dimethylthiourea, 1,1-diethylthiourea, 1,3-diethylthiourea, 1,3-dibutylthiourea, 1,3-diisopropylthiourea, 1,3-dicyclohexylthiourea, N,N-diphenylthiourea, N,N'-diphenylthiourea, 1,3-di(o-tolyl)thiourea, 1,3-di(p-tolyl)thiourea, 1-benzyl-3-phenylthiourea, 1-methyl-3-phenylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea, and ethylenethiourea. An example of the 3-substituted thiourea is trimethylthiourea, and an example of the 4-substituted thiourea is tetramethylthiourea or 1,1,3,3-tetraethylthiourea.
[0040] Among the urea compounds, urea derivatives or thiourea derivatives are preferred, and urea derivatives are more preferred, in that when used in an image display device with an interlayer filling structure, the decrease in transmittance in a high temperature environment is suppressed and the decrease in polarization degree is small (cross loss is suppressed). Among the urea derivatives, mono- or di-substituted ureas are preferred, and mono-substituted ureas are more preferred. Di-substituted ureas include 1,1-substituted ureas and 1,3-substituted ureas, and 1,3-substituted ureas are more preferred.
[0041] [Transparent protective film] The transparent protective film (hereinafter, simply referred to as "protective film") used in the present invention is attached to at least one side of the polarizing element via an adhesive layer. This transparent protective film is attached to one or both sides of the polarizing element, and it is more preferable that it is attached to both sides. In one embodiment, the protective film is attached to the polarizing element via an adhesive layer that is a layer containing a urea-based compound. In a configuration in which protective films are bonded to both sides of a polarizing element via adhesive layers, only one of the adhesive layers on both sides of the polarizing element may be the urea-based compound-containing layer of the present invention, but it is more preferable that both adhesive layers on both sides are the urea-based compound-containing layer of the present invention.
[0042] In recent years, in order to meet the demand for thinner polarizing plates, polarizing plates having a protective film on only one side of the polarizing element have been developed. Even in this configuration, it is preferable to laminate the protective film via the adhesive layer, which is the urea-based compound-containing layer of the present invention. A conceivable method for producing a polarizing plate having a protective film only on one side of a polarizing element is to first produce a polarizing plate in which protective films are attached to both sides via an adhesive layer, and then peel off one of the protective films. When such a production method is used, it does not matter whether only one of the adhesive layers is the urea-based compound-containing layer of the present invention, but it is more preferable that the urea-based compound-containing layer of the present invention is used on both sides of the polarizing element. When the urea compound-containing layer of the present invention is used as an adhesive layer on only one side of a polarizing element, it is preferable that the adhesive layer on the film side that is not to be peeled off is the urea compound-containing layer of the present invention.
[0043] The protective film may also have other optical functions, and may have a laminated structure in which other layers are further laminated. In this case, the thickness of the protective film is preferably thin from the viewpoint of optical properties, but if it is too thin, the strength decreases and the processability becomes poor. The appropriate thickness is 5 to 100 μm, preferably 10 to 80 μm, and more preferably 15 to 70 μm.
[0044] The protective film may be a cellulose acylate resin film, a polycarbonate resin film, a cycloolefin resin film such as norbornene, a (meth)acrylic polymer film, or a polyester resin film such as polyethylene terephthalate. In the case of a configuration having protective films on both sides of a polarizing element, when bonding is performed using a water-based adhesive such as a PVA adhesive, it is preferable that the protective film on at least one side be either a cellulose acylate film or a (meth)acrylic polymer film from the standpoint of moisture permeability, and of these, a cellulose acylate film is preferred.
[0045] At least one of the protective films may have a retardation function for the purpose of compensating for viewing angle, etc. In that case, the film itself may have a retardation function, may have a separate retardation layer, or may be a combination of both. In the above description, the film having phase difference function is directly attached to the polarizing element via an adhesive. However, the film may be attached to the polarizing element via a pressure-sensitive adhesive or adhesive via another protective film attached to the polarizing element.
[0046] [Method of manufacturing polarizing plate] The method for producing a polarizing plate according to the present embodiment includes a lamination step of laminating a polarizing element and a urea-based compound-containing layer containing at least one urea-based compound selected from the group consisting of urea, urea derivatives, thiourea, and thiourea derivatives, and a moisture content adjustment step. In the moisture content adjustment step, when producing a polarizing plate having the characteristic (a), the moisture content of the polarizing element is adjusted so that the moisture content of the polarizing element is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. The moisture content of the polarizing element can be adjusted according to the description of the moisture content of the polarizing element described above. In the moisture content adjustment step, when producing a polarizing plate having the characteristic (b), the moisture content of the polarizing plate is adjusted so that the moisture content of the polarizing plate is equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. The moisture content of the polarizing plate can be adjusted according to the description of the moisture content of the polarizing plate described above. The order of the lamination step and the moisture content adjusting step is not limited, and the lamination step and the moisture content adjusting step may be performed in parallel.
[0047] [Image display device configuration] The polarizing plate of the present invention is used in various image display devices such as liquid crystal display devices and organic EL display devices. In the case of an image display device having an interlayer filling configuration in which both sides of the polarizing plate are in contact with layers other than air layers, the transmittance is likely to decrease in a high-temperature environment. In the image display device using the polarizing plate of the present invention, even if the image display device has an interlayer filling configuration, the decrease in the transmittance of the polarizing plate in a high-temperature environment can be suppressed. An example of the image display device is a configuration having an image display cell, a first adhesive layer laminated on the viewing side surface of the image display cell, and a polarizing plate laminated on the viewing side surface of the first adhesive layer. Such an image display device may further have a second adhesive layer laminated on the viewing side surface of the polarizing plate and a transparent member laminated on the surface of the second adhesive layer. In particular, the polarizing plate of the present invention is suitably used in an image display device having an interlayer filling configuration in which a transparent member is arranged on the viewing side of the image display device, the polarizing plate and the image display cell are bonded together by the first adhesive layer, and the polarizing plate and the transparent member are bonded together by the second adhesive layer. In this specification, either one or both of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer may be simply referred to as an “adhesive layer.” Note that the member used for bonding the polarizing plate and the image display cell, or the polarizing plate and the transparent member is not limited to a pressure-sensitive adhesive layer, and may be an adhesive layer.
[0048] <Image display cell> Examples of the image display cell include a liquid crystal cell and an organic EL cell. The liquid crystal cell may be a reflective liquid crystal cell that uses external light, a transmissive liquid crystal cell that uses light from a light source such as a backlight, or a semi-transmissive semi-reflective liquid crystal cell that uses both external light and light from a light source. When the liquid crystal cell uses light from a light source, the image display device (liquid crystal display device) has a polarizing plate disposed on the opposite side to the viewing side of the image display cell (liquid crystal cell), and further has a light source disposed thereon. The polarizing plate on the light source side and the liquid crystal cell are preferably bonded together via an appropriate adhesive layer. The driving method of the liquid crystal cell may be any type, such as VA mode, IPS mode, TN mode, STN mode, or bend orientation (π type).
[0049] As the organic EL cell, a light-emitting body (organic electroluminescence light-emitting body) is preferably formed by sequentially laminating a transparent electrode, an organic light-emitting layer, and a metal electrode on a transparent substrate. The organic light-emitting layer is a laminate of various organic thin films, and various layer configurations can be adopted, such as a laminate of a hole injection layer made of a triphenylamine derivative or the like and a light-emitting layer made of a fluorescent organic solid such as anthracene, a laminate of these light-emitting layers and an electron injection layer made of a perylene derivative or the like, or a laminate of a hole injection layer, a light-emitting layer, and an electron injection layer.
[0050] <Laminating the image display cell and the polarizing plate> A pressure-sensitive adhesive layer (pressure-sensitive adhesive sheet) is preferably used for bonding the image display cell and the polarizing plate. Among them, a method of bonding a polarizing plate with a pressure-sensitive adhesive layer, in which a pressure-sensitive adhesive layer is attached to one side of the polarizing plate, to the image display cell is preferred from the viewpoint of workability and the like. The pressure-sensitive adhesive layer can be attached to the polarizing plate by a suitable method. For example, a pressure-sensitive adhesive solution of about 10 to 40% by weight is prepared by dissolving or dispersing a base polymer or a composition thereof in a solvent consisting of a single or mixture of suitable solvents such as toluene and ethyl acetate, and the solution is directly attached to the polarizing plate by a suitable spreading method such as a casting method or a coating method, or a method of forming a pressure-sensitive adhesive layer on a separator in accordance with the above and transferring the solution to the polarizing plate.
[0051] <Adhesive layer> The adhesive layer is described in paragraphs
[0103] to
[0143] of JP2018-025765A, and these adhesives can be used in the present invention.
[0052] <Transparent material> Examples of the transparent member arranged on the viewing side of the image display device include a front plate (window layer) and a touch panel. The front plate has appropriate mechanical strength and thickness. Examples of such a front plate include a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate. A functional layer such as an anti-reflection layer may be laminated on the viewing side of the front plate. In addition, when the front plate is a transparent resin plate, a hard coat layer may be laminated to increase physical strength, or a low moisture permeable layer may be laminated to reduce moisture permeability. As the touch panel, various touch panels such as resistive, capacitive, optical, and ultrasonic touch panels, as well as glass or transparent resin panels having a touch sensor function are used. When a capacitive touch panel is used as the transparent member, it is preferable that a front panel made of glass or transparent resin plate is provided on the viewing side further than the touch panel.
[0053] <Laminating polarizing plate and transparent material> A pressure sensitive adhesive or a UV curable adhesive is preferably used to bond the polarizing plate and the transparent member. When a pressure sensitive adhesive is used, the pressure sensitive adhesive can be applied by a suitable method. As a specific application method, for example, the application method of the pressure sensitive adhesive layer used in bonding the image display cell and the polarizing plate described above can be mentioned.
[0054] When using a UV-curing adhesive, a method is preferably used in which a dam material is provided around the periphery of the image display panel to prevent the adhesive solution from spreading before curing, a transparent member is placed on the dam material, and the adhesive solution is then poured in. After the adhesive solution is poured, alignment and degassing are performed as necessary, and then the adhesive solution is irradiated with UV light to cause curing.
[0055] Next, the urea compound-containing layer other than the adhesive layer will be described.
[0056] [Urea-based compound-containing layer (other than adhesive layer)] The urea-based compound-containing layer preferably contains at least one urea-based compound and a binder. Examples of the binder include a polymer binder, a thermosetting resin binder, and an active energy ray-curable resin binder, and any of these binders can be preferably used in the present invention.
[0057] The thickness of the urea compound-containing layer is preferably from 0.1 to 20 μm, more preferably from 0.5 to 15 μm, and further preferably from 1 to 10 μm. The urea-based compound-containing layer may be laminated directly to the polarizing element or may be laminated via another layer, but it is preferable that the urea-based compound-containing layer is laminated directly to and in contact with the polarizing element, since this makes it easier to prevent a decrease in transmittance in a high-temperature environment. A polarizing plate having a urea-based compound-containing layer other than the adhesive layer is preferably provided with a transparent protective film on at least one surface of the polarizing element via the adhesive layer in order to increase the physical strength of the polarizing plate. In this case, the adhesive layer may or may not contain a urea-based compound, but it is more preferable that the adhesive layer contains the urea-based compound.
[0058] As described in the explanation of the protective film, in recent years, in order to meet the demand for thinner polarizing plates, polarizing plates having a protective film on only one side of the polarizing element (hereinafter also referred to as "polarizing plates with one-sided protective film") have been developed. In order to increase the physical strength of such a configuration, attempts have been made to laminate a cured layer on the surface of the polarizing element that does not have a protective film (for example, JP 2011-221185 A).
[0059] In this embodiment, it is also a preferred embodiment to include a urea-based compound in such a cured layer to form a urea-based compound-containing layer. Usually, such a cured layer is formed from a curable composition containing an organic solvent, but paragraphs
[0020] to
[0042] of JP 2017-075986 A describe a method of forming such a cured layer from an aqueous solution of an active energy ray-curable polymer composition. Since many urea-based compounds are water-soluble, it is also a preferred embodiment of this embodiment to include a water-soluble urea-based compound in such a composition to form a urea-based compound-containing layer.
[0060] Second Embodiment The polarizing plate according to the second embodiment of the present invention includes a polarizing element having iodine adsorbed and aligned in a polyvinyl alcohol-based resin layer and containing at least one urea-based compound selected from urea, urea derivatives, thiourea, and thiourea derivatives, and a transparent protective film. The polarizing plate according to this embodiment has at least one of the following characteristics (a) and (b). (a) The moisture content of the polarizing element is equal to or greater than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and is equal to or less than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%. (b) The moisture content of the polarizing plate is equal to or greater than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and is equal to or less than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
[0061] The polarizing plate of this embodiment has at least one of the above characteristics (a) and (b), and further contains a urea-based compound in the polarizing element, so that the polarizing plate can be used in an image display device having an interlayer filling configuration, and can suppress a decrease in the single-unit transmittance even when exposed to a high-temperature environment for a long period of time. The polarizing plate of this embodiment contains a urea-based compound in the polarizing element, so that a decrease in the polarization degree can be suppressed even when the polarizing plate is exposed to a high-temperature environment, and cross-drop can also be easily suppressed.
[0062] The above features (a) and (b) are the same as the features (a) and (b) in the first embodiment.
[0063] The method for producing a polarizing element of this embodiment includes a step of making the polarizing element contain a urea-based compound in the method for producing a polarizing element described in the first embodiment. As a method for making the polarizing element contain a urea-based compound, a polarizing element containing a urea-based compound can be obtained by preparing a polarizing element through a step of applying a solution containing a urea-based compound to at least one surface of the polarizing element and drying the solution. In the manufacturing process of the polarizing element, the urea-based compound may be made to be contained in the polarizing element by a method of immersing a PVA-based resin layer in a treatment solution containing a urea-based compound, or a method of spraying, flowing or dripping the treatment solution onto the PVA-based resin layer. Among these, a method of immersing a PVA-based resin layer in a treatment solution containing a urea-based compound is preferably used.
[0064] The process of immersing the PVA-based resin layer in a treatment solution containing a urea-based compound may be carried out simultaneously with the processes of swelling, stretching, dyeing, crosslinking, washing, etc. in the manufacturing method of a polarizing element, or may be provided separately from these processes. The process of making the PVA-based resin layer contain a urea-based compound is preferably carried out after dyeing the PVA-based resin layer with iodine, and more preferably carried out simultaneously with the crosslinking process after dyeing. According to such a method, the change in hue is small, and the effect on the optical properties of the polarizing element can be reduced.
[0065] The type and content of the urea-based compound contained in the polarizing element of this embodiment are the same as those described for the urea-based compound-containing layer in the first embodiment. The polarizing element of this embodiment can also be used as the polarizing element of the polarizing plate in the first embodiment. The other configurations of the polarizing plate of this embodiment are the same as those of the first embodiment, except that the urea-based compound-containing layer in the first embodiment is an optional component.
[0066] [Urea compound solution] The solvent of the urea-based compound-containing solution used in this embodiment is preferably water, an organic solvent, or a mixture thereof, and more preferably either water or a mixed solvent of water and alcohol. In addition, in the case of a mixed solvent of water and alcohol, the alcohol is preferably either methanol or ethanol. As for the urea-based compound, as described in the first embodiment, it is preferable that the urea-based compound is water-soluble in order to prevent the urea-based compound from precipitating on the surface of the polarizing element after drying.
[0067] [Method of manufacturing polarizing plate] The method for producing a polarizing plate according to the present embodiment includes a moisture content adjusting step, which is similar to the method for producing a polarizing plate according to the first embodiment. EXAMPLES
[0068] The present invention will be specifically described below based on examples. The materials, reagents, amounts of substances and their ratios, operations, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the present invention is not limited to the following examples.
[0069] (Preparation of Polarizing Element 1) A 40 μm thick polyvinyl alcohol film made of polyvinyl alcohol with an average degree of polymerization of about 2,400 and a degree of saponification of 99.9 mol% or more was uniaxially stretched by about 5 times in a dry state, and then, while maintaining tension, was immersed in pure water at 60°C for 1 minute, and then immersed in an aqueous solution with a weight ratio of iodine / potassium iodide / water of 0.05 / 5 / 100 at 28°C for 60 seconds. Then, it was immersed in an aqueous solution with a weight ratio of potassium iodide / boric acid / water of 8.5 / 8.5 / 100 at 72°C for 300 seconds. It was then washed with pure water at 26°C for 20 seconds and dried at 65°C to obtain a polarizing element with a thickness of 15 μm in which iodine was adsorbed and aligned in the polyvinyl alcohol.
[0070] (Preparation of PVA solution for adhesive) 50 g of modified PVA resin containing acetoacetyl groups (Mitsubishi Chemical Corporation: Gohsenex Z-410) was dissolved in 950 g of pure water, heated at 90° C. for 2 hours, and then cooled to room temperature to obtain a PVA solution for adhesive.
[0071] (Preparation of urea compound solution) 10 g of urea was added to 90 g of pure water to obtain a 10 wt % urea aqueous solution (Solution 1). Similarly, according to Table 1, urea solutions 2 to 4 were prepared by replacing urea with the urea-based compounds shown in Table 1.
[0072] [Table 1]
[0073] The urea, methylurea, ethylurea, and tetrahydro-2-pyrimidinone used above were all reagents manufactured by Tokyo Chemical Industry Co., Ltd.
[0074] (Preparation of Polarizing Plate Adhesive 1) The PVA solution for adhesive, urea solution 1, pure water and methanol prepared above were mixed to give a PVA concentration of 3.0%, a methanol concentration of 20% and a urea concentration of 0.5%, to obtain an adhesive 1 for polarizing plates.
[0075] (Preparation of Polarizing Plate Adhesive 2) Similarly, the PVA solution for adhesive, urea solution 2 shown in Table 1, pure water and methanol were mixed to give a PVA concentration of 3.0%, a methanol concentration of 20% and a methylurea concentration of 0.7%, to obtain an adhesive 2 for polarizing plates.
[0076] (Preparation of Polarizing Plate Adhesive 3) Similarly, the PVA solution for adhesive, urea solution 3 shown in Table 1, pure water and methanol were mixed to give a PVA concentration of 3.0%, a methanol concentration of 20% and an ethylurea concentration of 1.0%, to obtain an adhesive 3 for polarizing plates.
[0077] (Preparation of Polarizing Plate Adhesive 4) Similarly, the PVA solution for adhesive, urea solution 4 shown in Table 1, pure water and methanol were mixed to give a PVA concentration of 3.0%, a methanol concentration of 20% and a tetrahydro-2-pyrimidinone concentration of 1.5% to obtain adhesive 4 for polarizing plates.
[0078] (Preparation of Polarizing Plate Adhesive 5) Similarly, the adhesive PVA solution, pure water and methanol were mixed so that the PVA concentration was 3.0% and the methanol concentration was 20%, to obtain an adhesive 5 for polarizing plates.
[0079] (Saponification of Cellulose Acylate Film) A commercially available cellulose acylate film TD40 (manufactured by Fujifilm Corporation: film thickness 40 μm) was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) kept at 55° C. for 2 minutes, then washed with water, and then immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25° C. for 30 seconds, and then passed through a water washing bath under running water for 30 seconds to neutralize the film. Then, the film was repeatedly drained with an air knife three times, and after removing the water, it was allowed to stay in a drying zone at 70° C. for 15 seconds and dried to produce a saponified film.
[0080] (Preparation of Polarizing Plate 1) The saponified cellulose acylate film prepared above was attached to both sides of the polarizing element 1 via polarizing plate adhesive 1, and the thickness of the adhesive layer after drying was adjusted to 100 nm on both sides. The films were then laminated using a roll laminator and dried at 60°C for 10 minutes to obtain polarizing plate 1 with cellulose acylate film on both sides.
[0081] (Preparation of Polarizing Plates 2 to 5) Polarizing plates 2 to 5 were produced in the same manner as polarizing plate 1, except that the adhesive 1 for polarizing plates was replaced with adhesives 2 to 5 for polarizing plates.
[0082] (Adjusting the moisture content of polarizing plates (polarizing elements)) The polarizing plates 1 to 5 obtained above were stored for 72 hours at a temperature of 20°C and a relative humidity of 30%, 35%, 40%, 45%, 50% or 55%. The moisture content was measured using the Karl Fischer method after 66, 69 and 72 hours of storage. The moisture content did not change after 66, 69 and 72 hours of storage under any humidity condition. Therefore, the moisture content of the polarizing plates 1 to 5 can be considered to be the same as the equilibrium moisture content in the 72-hour storage environment used in this experimental example. When the moisture content of the polarizing plate reaches equilibrium in a certain storage environment, the moisture content of the polarizing element in the polarizing plate can also be considered to have reached equilibrium in that storage environment. In addition, when the moisture content of the polarizing element in the polarizing plate reaches equilibrium in a certain storage environment, the moisture content of the polarizing plate can also be considered to have reached equilibrium in that storage environment.
[0083] (Preparation of Optical Laminate 1) With reference to the examples in JP 2018-025765 A, an acrylic adhesive (manufacturer: Lintec Corporation, product number: #7) was applied to both sides of the polarizing plate 1 prepared above to produce an optical laminate 1 having adhesive layers (first adhesive layer and second adhesive layer) with a thickness of 25 μm on both sides. (Preparation of Optical Laminates 2 to 5) Optical laminates 2 to 5 were produced in the same manner as in the optical laminate 1, except that polarizing plate 1 was replaced with polarizing plates 2 to 5.
[0084] [Examples 1 to 9, Comparative Examples 1 to 6] In Examples 1 to 9 and Comparative Examples 1 to 6, the optical laminates shown in Table 2 were used and stored for 72 hours under conditions of a temperature of 20° C. and a relative humidity of 35%, 40%, 45%, 50% or 55% so that the moisture content of the optical laminates used would be the equilibrium moisture content of the environment shown in Table 2. The moisture content of the optical laminates can be considered to have reached equilibrium with the moisture content of the storage environment, and the moisture contents of the polarizing plate and polarizing element in the optical laminates can also be considered to be the same as the moisture content of the optical laminate.
[0085] (Inspection polarizing plate 1) An acrylic adhesive (manufacturer: Lintec Corporation, product number: #7) was laminated only on one side of polarizing plate 1 to prepare polarizing plate for inspection 1. Polarizing plate for inspection 1 thus prepared was cut into a size of 50 mm x 100 mm so that the short side was parallel to the absorption axis, and the surface of the adhesive layer was attached to alkali-free glass (product name "EAGLE XG", manufactured by Corning Incorporated) to prepare sample 1 for cross evaluation.
[0086] [Evaluation of unit transmittance after high-temperature durability test (105℃)] The optical laminates 1 to 5 prepared above were each cut into a size of 50 mm x 100 mm so that the long sides were parallel to the absorption axis, and the surfaces of the first adhesive layer and the second adhesive layer were each bonded to alkali-free glass (product name "EAGLE XG", manufactured by Corning Incorporated) to prepare evaluation samples. This evaluation sample was subjected to a temperature of 50°C and a pressure of 5kgf / cm 2 (490.3kPa) for 1 hour, and then left for 24 hours in an environment with a temperature of 23°C and a relative humidity of 55%. Thereafter, the transmittance was measured (initial value), and the specimen was stored in a heated environment at a temperature of 105°C, with the transmittance measured every 50 hours from 100 to 200 hours. Evaluation was performed according to the following criteria, based on the time at which the transmittance had decreased by 5% or more from the initial value. The results are shown in Table 2. The decrease in transmittance after 200 hours is 5% or less: A The transmittance drops by 5% or more after 150 to 200 hours: B The transmittance drops by 5% or more after 100 to 150 hours: C The transmittance drops by 5% or more after 100 hours: D
[0087] [Evaluation of cloth loss after high temperature durability test] After the evaluation of the single transmittance evaluation sample after high temperature durability for 200 hours, the optical laminate and the cloth evaluation sample 1 that was not placed in the heating environment were arranged in a cross Nicol state and placed on a backlight. The surroundings were shaded, and the cross missing was visually evaluated according to the following criteria. Note that samples with a single transmittance reduction of 5% or more were excluded from the evaluation of cross missing because they had coloration due to polyenation. No cross-linking is observed: A Almost no cross-cutting is observed: B There is a slight cross-cut :C The crossover is clearly visible :D
[0088] [Table 2]
Claims
1. A polarizing plate having a polarizing element in which iodine is adsorbed and aligned in a polyvinyl alcohol-based resin layer, and a transparent protective film, a urea-based compound-containing layer containing at least one urea-based compound selected from the group consisting of urea derivatives, thiourea, and thiourea derivatives; The urea derivatives include methyl urea, ethyl urea, propyl urea, butyl urea, isobutyl urea, N-octadecyl urea, 2-hydroxyethyl urea, hydroxy urea, acetyl urea, allyl urea, 2-propynyl urea, cyclohexyl urea, phenyl urea, 3-hydroxyphenyl urea, (4-methoxyphenyl) urea, benzyl urea, benzoyl urea, o-tolyl urea, p-tolyl urea, 1,1-dimethyl urea, 1,3-dimethyl urea, 1,1-diethyl urea, 1,3-diethyl urea, 1,3-bis(hydroxymethyl) urea, 1,3-t tert-butyl urea, 1,3-dicyclohexyl urea, 1,3-diphenyl urea, 1,3-bis(4-methoxyphenyl) urea, 1-acetyl-3-methyl urea, 2-imidazolidinone (ethylene urea), tetrahydro-2-pyrimidinone (propylene urea), tetramethyl urea, 1,1,3,3-tetraethyl urea, 1,1,3,3-tetrabutyl urea, 1,3-dimethoxy-1,3-dimethyl urea, 1,3-dimethyl-2-imidazolidinone, or 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; The polarizing element has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
2. A polarizing plate having a polarizing element in which iodine is adsorbed and aligned in a polyvinyl alcohol-based resin layer, and a transparent protective film, a urea-based compound-containing layer containing at least one urea-based compound selected from the group consisting of urea derivatives, thiourea, and thiourea derivatives; The urea derivatives include methyl urea, ethyl urea, propyl urea, butyl urea, isobutyl urea, N-octadecyl urea, 2-hydroxyethyl urea, hydroxy urea, acetyl urea, allyl urea, 2-propynyl urea, cyclohexyl urea, phenyl urea, 3-hydroxyphenyl urea, (4-methoxyphenyl) urea, benzyl urea, benzoyl urea, o-tolyl urea, p-tolyl urea, 1,1-dimethyl urea, 1,3-dimethyl urea, 1,1-diethyl urea, 1,3-diethyl urea, 1,3-bis(hydroxymethyl) urea, 1,3-t tert-butyl urea, 1,3-dicyclohexyl urea, 1,3-diphenyl urea, 1,3-bis(4-methoxyphenyl) urea, 1-acetyl-3-methyl urea, 2-imidazolidinone (ethylene urea), tetrahydro-2-pyrimidinone (propylene urea), tetramethyl urea, 1,1,3,3-tetraethyl urea, 1,1,3,3-tetrabutyl urea, 1,3-dimethoxy-1,3-dimethyl urea, 1,3-dimethyl-2-imidazolidinone, or 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; The polarizing plate has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
3. 3. The polarizing plate according to claim 1, wherein the urea compound-containing layer contains at least one urea compound selected from the group consisting of urea derivatives and thiourea derivatives.
4. 4. The polarizing plate according to claim 1, wherein the urea compound-containing layer is in contact with the polarizing element.
5. 5. The polarizing plate according to claim 1, wherein the urea compound-containing layer is an adhesive layer.
6. The polarizing plate according to claim 5 , wherein the urea compound-containing layer contains a polyvinyl alcohol-based resin.
7. 7. The polarizing plate according to claim 6, wherein the total content of the urea compounds in the urea compound-containing layer is from 0.1 parts by mass to 400 parts by mass with respect to 100 parts by mass of the polyvinyl alcohol resin.
8. 8. The polarizing plate according to claim 5, wherein the urea compound-containing layer has a thickness of 0.01 to 7 μm.
9. A polarizing plate having a polarizing element in which iodine is adsorbed and aligned in a polyvinyl alcohol-based resin layer, and a transparent protective film, the polarizing element contains at least one urea-based compound selected from the group consisting of urea derivatives and thiourea derivatives, The urea derivatives include methyl urea, ethyl urea, propyl urea, butyl urea, isobutyl urea, N-octadecyl urea, 2-hydroxyethyl urea, hydroxy urea, acetyl urea, allyl urea, 2-propynyl urea, cyclohexyl urea, phenyl urea, 3-hydroxyphenyl urea, (4-methoxyphenyl) urea, benzyl urea, benzoyl urea, o-tolyl urea, p-tolyl urea, 1,1-dimethyl urea, 1,3-dimethyl urea, 1,1-diethyl urea, 1,3-diethyl urea, 1,3-bis(hydroxymethyl) urea, 1,3-t tert-butyl urea, 1,3-dicyclohexyl urea, 1,3-diphenyl urea, 1,3-bis(4-methoxyphenyl) urea, 1-acetyl-3-methyl urea, 2-imidazolidinone (ethylene urea), tetrahydro-2-pyrimidinone (propylene urea), tetramethyl urea, 1,1,3,3-tetraethyl urea, 1,1,3,3-tetrabutyl urea, 1,3-dimethoxy-1,3-dimethyl urea, 1,3-dimethyl-2-imidazolidinone, or 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; The polarizing element has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
10. A polarizing plate having a polarizing element in which iodine is adsorbed and aligned in a polyvinyl alcohol-based resin layer, and a transparent protective film, the polarizing element contains at least one urea-based compound selected from the group consisting of urea derivatives and thiourea derivatives, The urea derivatives include methyl urea, ethyl urea, propyl urea, butyl urea, isobutyl urea, N-octadecyl urea, 2-hydroxyethyl urea, hydroxy urea, acetyl urea, allyl urea, 2-propynyl urea, cyclohexyl urea, phenyl urea, 3-hydroxyphenyl urea, (4-methoxyphenyl) urea, benzyl urea, benzoyl urea, o-tolyl urea, p-tolyl urea, 1,1-dimethyl urea, 1,3-dimethyl urea, 1,1-diethyl urea, 1,3-diethyl urea, 1,3-bis(hydroxymethyl) urea, 1,3-t tert-butyl urea, 1,3-dicyclohexyl urea, 1,3-diphenyl urea, 1,3-bis(4-methoxyphenyl) urea, 1-acetyl-3-methyl urea, 2-imidazolidinone (ethylene urea), tetrahydro-2-pyrimidinone (propylene urea), tetramethyl urea, 1,1,3,3-tetraethyl urea, 1,1,3,3-tetrabutyl urea, 1,3-dimethoxy-1,3-dimethyl urea, 1,3-dimethyl-2-imidazolidinone, or 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone; The polarizing plate has a moisture content equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30%, and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
11. The polarizing plate is used in an image display device, 11. The polarizing plate according to claim 1, wherein in the image display device, a layer other than an air layer is provided on both sides of the polarizing plate in contact with the both sides.
12. An image display device comprising: an image display cell; a first adhesive layer laminated on a viewing side surface of the image display cell; and a polarizing plate according to any one of claims 1 to 11 laminated on the viewing side surface of the first adhesive layer.
13. The image display device according to claim 12 , further comprising: a second adhesive layer laminated on the viewer-side surface of the polarizing plate; and a transparent member laminated on the viewer-side surface of the second adhesive layer.
14. The image display device according to claim 13 , wherein the transparent member is a glass plate or a transparent resin plate.
15. The image display device according to claim 13 , wherein the transparent member is a touch panel.
16. A method for producing the polarizing plate according to claim 1 or 9, comprising the steps of: A method for producing a polarizing plate, comprising a moisture content adjusting step of adjusting the moisture content of the polarizing element so that it is equal to or higher than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20°C and a relative humidity of 50%.
17. A method for producing the polarizing plate according to claim 2 or 10, comprising the steps of: The method for producing a polarizing plate includes a moisture content adjusting step of adjusting the moisture content of the polarizing plate to be equal to or higher than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 30% and equal to or lower than the equilibrium moisture content at a temperature of 20° C. and a relative humidity of 50%.
Citation Information
Patent Citations
Method for laminating film for polarizing plate
JP1991064703A
Liquid crystal panel support, electronic equipment having the same and manufacture of the same equipment
JP1999174417A
Iodine-based polarizing plate and method for manufacturing the same
JP2003315537A
Method for manufacturing polarizer, and polarizer
JP2008102246A
Method for producing polarizer, polarizer produced thereby, polarizing plate and image display apparatus
JP2010276815A